Photocatalytic behavior of LiNbO3: a DFT-based investigation of electronic and optical properties - Zainuddin, Lili Widarti; Mohamad Taib, Mohamad Fariz (2024)
This study employs Density Functional Theory (DFT) to explain the photocatalytic mechanisms of Lithium Niobate (LiNbO3), a promising material for environmental and energy applications. The exchange correlation for this study is based on modified Perdew-Burke-Ernzerhof generalized gradient approximation for solids (GGA-PBEsol). The structural properties and electronic properties of LiNbO3 are comprehensively analyzed to understand its photocatalytic potential. From the band structure, calculations shows that LiNbO3 the band gap energy using GGAPBEsol is 3.48 eV. The optical absorption spectrum indicates strong absorption in the UV region which is agree the band gap value. The photocatalytic approach shows the theoretical process happend in the process.